Design and Development of the “Seruni Sehat” Application: A Health Functional Competency Test Registration System for the West Kalimantan Provincial Health Service - Suharsono Suharsono; Agung Sutiyo Sudrajat; Muhammad Hasbi; Tri Bowo Atmojo (Politeknik Pertanian Negeri Samarinda, 2025)
The West Kalimantan Province Health Service has a competency test registration service for promotions to functional positions for health workers via Google Form, however, the use of Google Form does not support registration, so it has difficulty verifying the Competency Test registration files. So it takes a long time to check each registrant one by one manually. For this reason, the West Kalimantan Health Functional Competency Test Registration System Application was created which is expected to make it easier for registrants and admins in the Health Human Resources, Data, and Health Information Technology fields to verify participant files. The development method used in making this application is the Waterfall method. The waterfall method is a systematic development method that goes from one stage to another. The essence of the waterfall method is that work on a system is carried out sequentially or linearly. Meanwhile, the software that will be used to build this application is Laravel, Bootstrap, and PHP. This research produced the Application which can provide registration services, upload files for competency tests, view data that has been registered, correct data if it needs to be corrected, and also print competency test participant cards. Based on the results of application testing which has been carried out by testing directly with the Admin of the West Kalimantan Provincial Health Service, it is running as it should.